Effect of Crop Residue and Potassium Management Practices on Growth and Yield of Wheat (Triticum aestivum L.) - Arora, Kajal; Bana, R.S.; Kumar, Avaneesh (Annals of Arid Zone, 2023)
An investigation was carried out at ICAR-Indian Agricultural Research Institute(IARI), New Delhi during rabi seasons of 2020-21, with the objective to determinebetter crop residue and potassium management practices for growth parameters andtheir impact on yield of wheat. The experiment was laid out in split-plot design withthree replications having three residue management treatments in main plot and fivepotassium management practices [Control (no application of fertilizer, (K1), 50% ofRDK (K2), 100% of RDK (K3), 50% of RDK (½ basal + ½ top dress at 25 DAS, (K4) and100% RDK (½ basal + ½ top dress at 25 DAS), (K5)] in sub-plot. Results indicated thatthe higher values of all the growth parameters, grain, straw yield and harvest index ofwheat was recorded with the crop residue retention @ 3t ha -1 with the split applicationof 100% recommended dose of potassium (½ at basal + ½ top dress at 25 DAS).